Development of maternal and foetal immune responses in cattle following experimental challenge with Neospora caninum at day 210 of gestation - Bartley, Paul M. (2013)
This study examined the immunological responses of pregnant cattle and their foetuses following an experimental challenge with live Neospora caninum tachyzoites at day 210 of gestation. Animals were bled prior to and weekly throughout the experiment and sacrificed at 14, 28, 42 and 56 days post inoculation (dpi). At post mortem examination, samples of lymph nodes and spleen were collected from both dam and foetus for immunological analysis. Subcutaneous (sc) inoculation over the left prefemoral (LPF) lymph node of pregnant cattle at day 210 of gestation, led to the vertical transmission of parasites by 14 dpi, however no foetal deaths were observed in the infected animals. Foetuses from infected dams mounted Neospora-specific humoral and cell-mediated immune (CMI) responses by 14 dpi. These responses involved anti-Neospora IgG, antigen-specific lymphocyte proliferation, and the production of the cytokines IFN–γ, interleukin (IL)-4 and IL-10. There was also evidence of innate immunity during the response against Neospora from infected dams, with statistically significant (p < 0.05) increases in mean expression of toll like receptors (TLR)-2 on 56 dpi in maternal spleen, LPF, right prefemoral (RPF), left uterine (LUL) and right uterine (RUL) lymph nodes and TLR-9 in retropharyngeal (RLN), LPF and RPF lymph nodes from 28 dpi. Statistically significant (p < 0.05) increases in mean TLR-9 were detected in spleen samples from foetuses of infected dams, compared to the foetuses from control animals. Our results show that vertical transmission of the parasite occurred in all infected dams, with their foetuses showing effective Neospora-specific cell mediated, humoral and innate immune responses.